Habitual Breakfast-Skipping as Predictor of Health Quality among Young Women - Sherwani, Rabiah; Masood, Afsheen; Sherwani, Hafsah (International Health Review, 2024)
Breakfast-skipping habit is quite common among women, especially adolescent girls. Resultantly, their mental health, physical activity level, and menstruation cycle get affected. A quantitative study was conducted to determine this phenomenon. The objective of this study was to determine the effect of breakfast-skipping habits on mental health, physical activity level, and menstruation cycle among women of ages ranging between 18-24 years. A sample of 93 women was selected from different colleges in Lahore. Their demographics, breakfast-skipping habits, mental health, physical activity level, and menstruation cycle irregularities were determined through different tools. The results showed that there was a significant relationship between breakfast-skipping habits, mental health, physical activity level as well as menstrual irregularities. Breakfast-skipping habits predicted the menstrual irregularities significantly (P=0.02*). It was inferred that school and college girls who skip their breakfast daily, suffer from poor mental health and menstrual problems. They were also less active and participated in fewer physical activities. The current study may be further implicated among adolescent girls to have a good breakfast for improved mental health, physical activity level, and menstrual irregularities.